Analisis Pengaruh Kualitas Produk, Kualitas Pelayanan, Harga Dan Promosi Terhadap Keputusan Pembelian Produk Tahu Bakso Kenari Di Solo Raya - Azzahra Putri, Inas; Mutiasari, Annisa Indah; Cahyani, Rusnandari Retno (STIM-LPI Makassar, 2024)
This research aims to analyze the influence of product quality, service quality, price and promotion on purchasing decisions for Tofu Bakso Kenari products in Solo Raya . The main focus of this research is to determine the extent to which product quality influences consumer purchasing decisions. The research method used is quantitative descriptive using external data sources obtained through questionnaires distributed to consumers of Kenari Meatball Tofu products. The sampling technique used was non-probability sampling with purposive sampling, which allows the selection of respondents based on certain criteria that are relevant to this research. This research concludes that product quality and promotion have a significant influence on purchasing decisions for Kenari Tahu Bakso in Solo Raya, while service quality and price do not have a significant influence. The implications of this research can be used as a guide for producers in improving their marketing strategies.